2018
DOI: 10.1002/hrm.21903
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between innovation‐led HR policy, strategy, and firm performance: A serial mediation investigation

Abstract: This research examines the relationship between innovation‐led strategy and innovation‐led HR policy (hereafter, management initiatives) and innovation performance. Our research model is theorized and tested in the Vietnamese context, based on the servant leadership theory and componential theory of creativity. We draw upon constructs of management initiatives, servant leadership, employee creativity, and firm innovation to hypothesize serial mediation mechanisms linking management initiatives to firm performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 117 publications
3
71
0
1
Order By: Relevance
“…Research at the LTMM level has considered various types of HRM content, from individual high-performance HRM practices (e.g., Han, Bartol, & Kim, 2015; Pak & Kim, 2018; Vermeeren, 2014) to systems or bundles of HRM content (e.g., Chuang, Jackson, & Jiang, 2016; Do, Budhwar, & Patel, 2018; Jiang, Chuang, & Chiao, 2015; Neves, Almeida, & Velez, 2018; Sikora et al, 2015). However, despite the considerable breadth of HRM content considered, our review suggests that little research has been done on the roles that LTMMs play in an organization’s adoption of this content.…”
Section: The Roles Of Ltmms In Hrm Researchmentioning
confidence: 99%
“…Research at the LTMM level has considered various types of HRM content, from individual high-performance HRM practices (e.g., Han, Bartol, & Kim, 2015; Pak & Kim, 2018; Vermeeren, 2014) to systems or bundles of HRM content (e.g., Chuang, Jackson, & Jiang, 2016; Do, Budhwar, & Patel, 2018; Jiang, Chuang, & Chiao, 2015; Neves, Almeida, & Velez, 2018; Sikora et al, 2015). However, despite the considerable breadth of HRM content considered, our review suggests that little research has been done on the roles that LTMMs play in an organization’s adoption of this content.…”
Section: The Roles Of Ltmms In Hrm Researchmentioning
confidence: 99%
“…Prior research has also suggested that HPWS may generate the capacity for innovation (Do, Budhwar, & Patel, 2018; Fu, Flood, Bosak, Morris, & O'Regan, 2015; Sung & Choi, 2018). While HPWS do not themselves constitute a source of competitive advantage, they may serve to generate a unique set of HRM attributes to do so (Beugelsdijk, 2008; Colbert, 2004; Patel, Messersmith, & Lepak, 2013).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Innovative behavior has quickly become a growing area of interest in HRM literature (Cooke & Saini, ), with several studies demonstrating a positive link between empowering HRM practices and innovative employee behavior (e.g., Do, Budhwar, & Patel, ; Y. Zhou, Hong, & Liu, ). Innovation comprises idea generation , occurring when employees generate new ideas through exploration, experimentation, and risk taking (Miron‐Spektor, Erez, & Naveh, ), and idea implementation , in which employees and the organization put ideas into practice, which generally requires support (resources, funding, and time), integration with existing systems, and revision of the ideas (Alexander & Van Knippenberg, ; West, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Innovative behavior has quickly become a growing area of interest in HRM literature (Cooke & Saini, 2010), with several studies demonstrating a positive link between empowering HRM practices and innovative employee behavior (e.g., Do, Budhwar, & Patel, 2018;Y. Zhou, Hong, & Liu, 2013).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%